2004
DOI: 10.1093/toxsci/kfh147
|View full text |Cite
|
Sign up to set email alerts
|

Phytoestrogens and Their Human Metabolites Show Distinct Agonistic and Antagonistic Properties on Estrogen Receptor   (ER ) and ER  in Human Cells

Abstract: Phytoestrogens exert pleiotropic effects on cellular signaling and show some beneficial effects on estrogen-dependent diseases. However, due to activation/inhibition of the estrogen receptors ERalpha or ERbeta, these compounds may induce or inhibit estrogen action and, therefore, have the potential to disrupt estrogen signaling. We performed a comprehensive analysis and potency comparison of phytoestrogens and their human metabolites for ER binding, induction/suppression of ERalpha and ERbeta transactivation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
319
1
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 489 publications
(340 citation statements)
references
References 48 publications
14
319
1
6
Order By: Relevance
“…Although genestein has a greater affinity for the ERb than the ERa subtype (Kuiper et al, 1997;Kostelac et al, 2003;Mueller et al, 2004;Zhao and Brinton, 2005;McCarty, 2006), it does have the potential to act as a full agonist at both these ER subtypes (Mueller et al, 2004;McCarty, 2006). However, as the vaginal cytology of the OVX + DMSO control rats did not show any evidence of vaginal cornification, we do not believe that exposure to phytoestrogens in the rat food led to any significant activation of the ERa subtype.…”
Section: Consideration Of Study Limitationsmentioning
confidence: 75%
“…Although genestein has a greater affinity for the ERb than the ERa subtype (Kuiper et al, 1997;Kostelac et al, 2003;Mueller et al, 2004;Zhao and Brinton, 2005;McCarty, 2006), it does have the potential to act as a full agonist at both these ER subtypes (Mueller et al, 2004;McCarty, 2006). However, as the vaginal cytology of the OVX + DMSO control rats did not show any evidence of vaginal cornification, we do not believe that exposure to phytoestrogens in the rat food led to any significant activation of the ERa subtype.…”
Section: Consideration Of Study Limitationsmentioning
confidence: 75%
“…In general, the affinity of flavonoids to bind to ERa and b is lower than that of 17-bestradiol. However, some studies have confirmed that genistein, daidzein, and equol have a good affinity for ER, especially for ERb (Mueller et al 2004).…”
Section: Relative Affinity For Era and Erbmentioning
confidence: 99%
“…AF-1 domains of each receptor play a critical role in their activity, but ligands determine biological responses [23][24][25][26]. SERMS, phytoestrogens, derivatives, and metabolites exhibit ER isoform specificity in binding and activation in different cell and promoter contexts [20][21][22][23][24][25].…”
Section: Erα and Erβ Activity -Homodimers And Heterodimers A Transcrmentioning
confidence: 99%